2019
DOI: 10.1007/s42452-019-0643-9
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid geothermal–PV–wind system for a village in Pakistan

Abstract: Combining diverse sources of renewable power into a hybrid renewable energy system (HRES) has gained more attractions with the fast evolution of the renewable energy market. Renewable resources as alternative energy for electricity generation are the only way to cater to the present environmental and social challenges. An on-grid hybrid geothermal-PV-wind system at Tattapani, Azad Jammu Kashmir, Pakistan, is considered, as enough geothermal energy is available from hot springs to cater for the perennial base l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This includes: hybrid single-flash and double-flash systems, hybrid flash-binary configuration and hybrid fossil geothermal technology [23,30]. In addition, the development of hybrid power systems integrating geothermal plants with biomass, fuel cells, wind, solar systems and waste-to-energy (WTE) technologies has been gaining a lot of interest [31][32][33][34][35].…”
Section: Binary Cycle Power Plantsmentioning
confidence: 99%
“…This includes: hybrid single-flash and double-flash systems, hybrid flash-binary configuration and hybrid fossil geothermal technology [23,30]. In addition, the development of hybrid power systems integrating geothermal plants with biomass, fuel cells, wind, solar systems and waste-to-energy (WTE) technologies has been gaining a lot of interest [31][32][33][34][35].…”
Section: Binary Cycle Power Plantsmentioning
confidence: 99%
“…A village named as Saeedpur Takkar near Mulaqatiar Road Tando Muhammad Khan, Sindh is selected for the case study as shown in Figure 2. This village is located at the latitude 25.1326'N and longitude 68.4539'E (7) . It consists around 85 houses, some shops and a secondary school.…”
Section: Study Areamentioning
confidence: 99%
“…Younas et al [10] and Mehmood et al [11] explored the geothermal energy potential for electric power generation. Other studies, such as Kazmi and Sheikh [12] and Shah [13], focused on designing hybrid energy systems and exploring different renewable energy sources. These studies help understand the potential of geothermal energy in Pakistan for sustainability and economic development [14].…”
Section: Introductionmentioning
confidence: 99%